2021
DOI: 10.1136/postgradmedj-2021-140971
|View full text |Cite
|
Sign up to set email alerts
|

Medical management for the prevention of kidney stones

Abstract: The alarming fact is that approximately one out of every 10 of us will have a kidney stone during our lifetime. The increasing prevalence and associated costs of kidney stones have resulted in it being one of the most commonly encountered and impactful medical conditions. Contributing factors include, but are not limited to, diet, climate, genetics, medications, activity and underlying medical conditions. Symptoms generally parallel stone size. Treatment varies from supportive to procedural (invasive and non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The study also highlighted the 'stone belt' phenomenon with Pakistan's inclusion in this high-prevalence geographical zone, further emphasizing the influence of environmental factors, particularly temperature, on the epidemiology of nephrolithiasis. This is consistent with the notion that geographical and climatic conditions play a non-negligible role in the pathogenesis of kidney stones (5,7,9). The current research has its strengths, including the comprehensive sampling from various localities, encompassing both rural and urban areas, and spanning a wide age range.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The study also highlighted the 'stone belt' phenomenon with Pakistan's inclusion in this high-prevalence geographical zone, further emphasizing the influence of environmental factors, particularly temperature, on the epidemiology of nephrolithiasis. This is consistent with the notion that geographical and climatic conditions play a non-negligible role in the pathogenesis of kidney stones (5,7,9). The current research has its strengths, including the comprehensive sampling from various localities, encompassing both rural and urban areas, and spanning a wide age range.…”
Section: Discussionsupporting
confidence: 86%
“…The disease's prevalence is not limited by gender, race, or age and varies significantly across geographical locations. Risk factors contributing to kidney stone formation include climatic conditions, particularly warmer climates and insufficient fluid intake, dietary patterns such as high salt and animal protein intake and low fiber diets, and certain medical conditions (8,9). These conditions include those that lead to increased serum calcium levels, like primary hyperparathyroidism, and metabolic disorders such as diabetes, stomach diseases, cardiovascular and liver diseases, obesity, high creatinine and uric acid levels, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrolithiasis is a common disease in the general population, with an estimated prevalence of 10%–15% ( 13 , 14 ). This condition is a considerable economic burden, costing the healthcare system more than $10 billion per year ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney stone is a common disease in urology, which can cause urinary tract obstruction and affect kidney function in serious cases [ 1 4 ]. Currently, the incidence of kidney stone is increasing year by year, with about 7%-13% in North America, 5%-9% in Europe, 1%-5% in Asia, and 6.3% in China [ 5 7 ]. In addition, kidney stone is also known as a lifelong disease because of the high recurrence rate, and it has been reported that about half of the patients with kidney stone disease would experience a second attack, and more than 10% experience more recurrence [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%